PEMBERDAYAAN MASYARAKAT MELALUI USAHA PERTAMBAKAN BERDASARKAN POTENSI KUALITAS AIR SUNGAI KRUENG CUNDA DI KOTA LHOKSEUMAWE - Ekamaida Ekamaida (LPPM Universitas Malikussaleh – Indonesia, 2017)
The city of Lhokseumawe is located in the coastal area of Malacca Strait separated through the river Krueng Cunda which forms a strait so potential to be used as aquaculture area. Determination of location of research by purposive sampling at River Krueng Cunda by setting five observation station. Sampling is done directly (insitu) location without repetition The result of water quality measurement at research location is measurement of chemical physics factor obtained average temperature 29 0C to 33 0C, dissolved oxygen (DO) 6,3 (mg / l) to 7, 7 (mg / l), the pH of the waters to five stations is in the range of 7.3 to 7.9 and the salinity in the station ranges from 12% to 28%. The quality of Krueng Cunda River water is still within the quality standard threshold according to Government Regulation No. 82 of 2001 on water quality management and water pollution control, so potential to be developed into aquaculture area.